Adequate Placental Sampling for the Diagnosis and Characterization of Placental Infection by Zika Virus - Venceslau, Emanuella Meneses; Guida, José Paulo Siqueira; Nobrega, Guilherme de Moraes; Samogim, Ana Paula; Parise, Pierina Lorencini; Japecanga, Rodolfo Rosa; Toledo-Teixeira, Daniel Augusto de; Forato, Julia; Antolini-Tavares, Arthur; Souza, Arethusa; Altemani, Albina; Consonni, Silvio Roberto; et al. (Frontiers in Microbiology, 2020)
The detection of Zika virus (ZIKV) in immunoprivileged anatomical sites, potential sites for viral persistence, may guide the confirmation of undefined cases of ZIKV infection and also bring to light unknown pathways of viral transmission. Thus, this study aimed to characterize ZIKV infection in stratified, standardized placental samples in women with exanthematic febrile manifestations during pregnancy and compare findings to the standard investigation protocol of official health agencies. To this end, a case series of placental findings within a prospective cohort study was conducted over a period of 24 months. Serum/urine were obtained at the time of clinical case identification. Placental sampling was performed following standard investigation protocol (samples of 1.0 cm sent to a reference laboratory) and in a systematic way at various regions, such as chorionic plate, chorionic villi, basal plate, amniotic membrane and umbilical cord, for subsequent ZIKV identification and quantification. Clinical information was obtained and histological preparation with Hematoxylin/Eosin staining for morphological evaluation was performed. This case series included 17 placentas systematically collected. Of these, 14 were positive by qRT-PCR for ZIKV, 5 in the umbilical cord, 7 in the amniotic membrane, 7 in the chorionic plate, 13 in the chorionic villi, and 7 in the basal plate, whereas none were reported by the reference laboratory. The most common morphological and anatomopathological findings were increased stromal cellularity, villitis, calcification, maternal vascular malperfusion, placental hypoplasia, and maternal-fetal hemorrhage (intervillous thrombi). Seven women presented positive testing for ZIKV in serological and/or molecular tests during gestation in urine. While viral quantification in urine ranged from 101 to 103 FFU eq/ml, that in different placental regions ranged from 103 to 108 FFU eq/g. Thus, ZIKV can infect different regions of the placenta and umbilical cord of pregnant women, showing that the systematic collection and adequate storage of the placenta is fundamental for the detection of ZIKV in this organ. The detection of ZIKV in the placenta after several months of initial symptoms suggests that this tissue may be a site for viral persistence during pregnancy